Resolving the Mystery of Ring Opening in the Synthesis of Benzo[d][1, 3]oxazin-4-one and Quinazolin-4(3H)-one - Patel, Harun; Pawara, Rahul; Surana, Sanjay (Letters in Organic Chemistry, 2019)
Quinazoline is the six-membered heterocyclic ring system reported for its versatile biological activities. This characteristic feature of quinazoline makes it a good template for a lead generation library. Ring opening is one of the major concerns in the synthesis of quinazolin-4(3H)-one that results in diamide formation. Here, alternative fusion strategy is reported, which is a time-saving and costeffective method to overcome the ring opening problem associated with the synthesis of benzo[ d][1,3]oxazin-4-one and quinazolin-4(3H)-one.
Keywords: ring opening